2019
DOI: 10.1186/s13075-019-2030-8
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic progression can still occur in individual patients with low or moderate disease activity in the current treat-to-target paradigm: real-world data from the Dutch Rheumatoid Arthritis Monitoring (DREAM) registry

Abstract: BackgroundThe aim of this retrospective study was to examine the longitudinal association between disease activity and radiographic damage in a cohort of patients with early RA (symptom onset < 1 year) treated according to treat-to-target (T2T) therapy.MethodsBaseline to 3-year follow-up data were used from patients included in the DREAM remission induction cohort. Patients received protocolized T2T treatment, aimed at 28-joint disease activity score-erythrocyte sedimentation rate (DAS28-ESR) remission. Diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…Several studies have previously been conducted analyzing selections of ADRs for specific types of DMARDs in specific treatment cohorts in DREAM-RA [6,7,8,9]. However, the question remains whether the frequency of the real-world reported ADRs in RA patients in the DREAM-RA registry matches with data in the SmPC.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have previously been conducted analyzing selections of ADRs for specific types of DMARDs in specific treatment cohorts in DREAM-RA [6,7,8,9]. However, the question remains whether the frequency of the real-world reported ADRs in RA patients in the DREAM-RA registry matches with data in the SmPC.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been convincingly demonstrated that these assumptions are rarely met, and that "between-person" relations can be quite different from "within-person" relations both in magnitude and sometimes even in direction [16][17][18][19][20]: an observation referred to as Simpson's paradox [21]. For instance, our study examining the association between disease activity and radiographic progression in RA patients showed that different indices of disease activity were not or only weakly associated at the "between-patient" level, but more often and more strongly associated within individual patients over time [22].…”
Section: Introductionmentioning
confidence: 81%
“…Interestingly, when following disease activity in individual patients over time, in patients in whom REM/LDA is achieved at endpoint, a drop in activity is already discernible within 4–12 weeks, in line with the treat-to-target recommendations2 and independent of whether patients have established or early RA. In contrast, those who remain in MDA/HDA never achieve any better status 30. The visualisation as ‘heatmaps’ allowed us to show these data for individual patients very clearly.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, those who remain in MDA/HDA never achieve any better status. 30 The visualisation as ‘heatmaps’ allowed us to show these data for individual patients very clearly. Another strength is the use of the CDAI for clinical disease activity assessment rather than a single measure.…”
Section: Discussionmentioning
confidence: 99%